The Effectiveness of Cognitive Restructuring Techniques to Improve of Comprehension of Drug Abusers Among Student - Amri Love Lindra; Yeni Karneli; Marlina Marlina (Journal of Educational and Learning Studies, 2020)
Incorrect understanding of the dangers of drug abuse makes adolescents underestimate the dangers of drug abuse. Most drug users in adolescence, because adolescents have unstable and easily influenced characteristics and great curiosity. Drug use by adolescents in the early stages is trying to the stage of addiction. The purpose of this study is to look at the effectiveness of cognitive restructuring techniques in increasing understanding of the dangers of student drug abuse. This study uses in the form of a pseudo experimental design of The Non-Equivalent Control Group with pretest and posttest. The subjects of the study were students of class X TKR at SMK Muhammadiyah 1 Padang with a sample of 20 people divided into 2 groups consisting of 10 people as the experimental group and 10 people as the control group. The sampling technique with purposive sampling technique. Data were analyzed using Wilcoxon signed ranks test and Kolmogorov Smirnov two independent samples. The results of this study, concluded that cognitive restructuring techniques are effective in increasing understanding of the dangers of student drug abuse.